Quantifying morphological stage to improve crop management and enhance yield and quality of sulla and lucerne - Borreani G.; Tabacco E.; Cavallarin L.; Peiretti P.G.; Re G.A.; Roggero P.P.; Sargenti P.; Sulas L. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
A better knowledge of forage legume production physiology in different environments is necessary to exploit their potential, through new harvesting and grazing systems. The paper reports the results of several experiments under different environmental conditions on lucerne (Po Valley) and sulla (Sardinia and central Italy) with the aim of relating the codified stage to forage quality. The OM digestibility, which is known to be the most important determinant of the nutritive value of forage, resulted to be inversely related to the stage evolution of both legumes. The use of the quantified morphological stage proved to be an easy pre-harvest tool to enhance yield and quality of legumes and to determine cutting or grazing schedules, for a profitable management of the crop.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)